2009
DOI: 10.14195/1647-8614_43-1_3
|View full text |Cite
|
Sign up to set email alerts
|

O uso dos jogos teatrais na educação: possibilidades diante do fracasso escolar

Abstract: Este artigo se refere ao uso do teatro na educação, sobretudo com crianças em situação de fracasso escolar. Pretende-se aqui descrever um dos seis casos estudados em pesquisa participante, realizada com crianças na referida situação, apresentando diversas dificuldades de aprendizagem, e encaminhadas por suas professoras. A partir das queixas escolares manifestadas, elaborou-se um programa de vivências semanais de jogos teatrais durante o período de um ano. Tal programa foi montado tendo em vista a promoção e a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
1
2
0
4
Order By: Relevance
“…Such data show a mismatch with the proposed by Lahire (2004), who mentioned that parents can assist in the learning process by means of transmission of values that refer to the importance of studying, of knowing how to read and write. However, some of the parents have shown not knowing what to do for their children to be interested in school, which converges with the data of the study conducted by Neves & Santiago (2009), in which a mother revealed that she beat her daughter and grounded her, but nothing would do her to get a better school performance. So, parents often do not have guidance on how to act with their children in relation to school involvement and a partnership with the school would be beneficial in this regard.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Such data show a mismatch with the proposed by Lahire (2004), who mentioned that parents can assist in the learning process by means of transmission of values that refer to the importance of studying, of knowing how to read and write. However, some of the parents have shown not knowing what to do for their children to be interested in school, which converges with the data of the study conducted by Neves & Santiago (2009), in which a mother revealed that she beat her daughter and grounded her, but nothing would do her to get a better school performance. So, parents often do not have guidance on how to act with their children in relation to school involvement and a partnership with the school would be beneficial in this regard.…”
Section: Discussionsupporting
confidence: 71%
“…In this sense, different researchers have worked to know the students' vision on the school failure (Farid, 2012;Guler, 2013;Hancer, 2012, Lagana-Riordan et al, 2011Oliveira & Macedo, 2011;Osti & Brenelli, 2013), as well as their family (Chechia & Andrade, 2005;Costa et al, 2010;Marchesi & Lucena, 2004;Martinelli & Aguena, 2011;Neves & Santiago, 2009) or their teachers (Asbahr & Lopes, 2006;Bray & Leonardo, 2011;Gomes & Souza, 2009;Hjörne & Säljö, 2014;Kamal & Bener, 2009). However, there are few studies that investigate and relate all the mentioned systems (Ireland et al, 2007;Marchesi & Lucena, 2004;Neves & Almeida, 1996).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A prática da Conversação, com o uso do Teatro, permite a participação dos múltiplos recursos que envolvem essa arte -a construção dramatúrgica, a construção de personagens, a improvisação, a interpretação ou a representação 6 . Tais recursos são geralmente explorados e propostos a partir de Jogos Teatrais (Neves & Santiago, 2009).…”
Section: A Conversação De Orientação Psicanalítica E O Teatro Como Meunclassified
“…Diversos pesquisadores têm concordado com a inserção de expressões artísticas no ensino de Ciências e Biologia, assim como na formação docente na área, de modo a garantir que a criatividade e a inovação façam parte do processo educativo dessas áreas do conhecimento. Assim, o teatro surge como um dos métodos empregados, visto que exige a presença da pessoa de forma completa: o corpo, a fala, o raciocínio e a emoção totalmente empregados no desenho e na apresentação da ideia a ser encenada, envolvendo tanto aspectos cognitivos quanto subjetivos dos sujeitos (NEVES; SANTIAGO, 2009).…”
Section: Introductionunclassified